Changes in the TNF-alpha/IL-10 ratio in hyperglycemia-associated pregnancies - Moreli, Jusciele B. [UNESP]; Correa-Silva, Simone [UNESP]; Damasceno, Débora Cristina [UNESP]; Sinzato, Yuri K. [UNESP]; Lorenzon-Ojea, Aline R.; Borbely, Alexandre U.; Rudge, Marilza Vieira Cunha [UNESP]; Bevilacqua, Estela; Calderon, Iracema M. P. [UNESP] (Elsevier B.V., 2015)
Aims: TNF-alpha is a diabetogenic cytokine associated with adverse outcomes during pregnancy that can be counterbalanced by IL-10. We have investigated IL-10 and TNF-alpha balance at maternal and placental levels in hyperglycemia-associated pregnancies.Methods: One hundred and ninety-two pregnant women participated, which included normoglycemic women (ND) and women with mild gestational hyperglycemia (MGH), gestational diabetes mellitus (GDM) and type 2 diabetes mellitus (DM2). Maternal plasma and placental tissue IL-10 and TNF-alpha levels were measured by ELISA and placental TNF-alpha was also immunolocalized.Results: Maternal plasma TNF-alpha levels were highest in GDM (p = 0.0190), whereas TNF-alpha levels were highest in placental tissues in DM2 (p = 0.0095). Immunohistochemistry also showed strong reactivity with anti-TNF-alpha antibody in the villous structures in the DM2 group. Conversely, IL-10 levels were lowest in maternal plasma of the DM2 group (p = 0.0228). The TNF-alpha/IL-10 ratio in maternal plasma progressively increased with the severity of hyperglycemia (p < 0.0001), being highest in placenta of the DM2 group (p = 0.0150). In both, plasma and placenta, TNF-alpha/IL-10 ratio were correlated with mean maternal glycemia and HbA1c levels.Conclusions: Alterations of placenta and serum TNF-alpha/IL-10 balance with predominance of TNF-alpha were correlated with the severity of hyperglycemia during gestation. This association may offer insight into the pathogenesis of gestational hyperglycemia and associated pregnancy outcomes. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: Cytokines; Diabetes; Mild gestational hyperglycemia; Placenta